2013
DOI: 10.3109/13880209.2013.777930
|View full text |Cite
|
Sign up to set email alerts
|

Brine shrimp lethality assay ‘an effective prescreen’: Microwave-assisted synthesis, BSL toxicity and 3DQSAR studies-based designing, docking and antitumor evaluation of potent chalcones

Abstract: The study draws a very good relationship between a simple, inexpensive, and bench-top BSL assay and the antitumor potential of the cytotoxic compounds. Devising the CoMFA analysis helped in designing chalcones with improved cytotoxic potential as displayed through their BSL and cytotoxic activity against human tumor cell lines. The studies are noteworthy as such comprehensive studies were never performed before on the BSL assay. The present studies widen the scope of the BSL model that may prove quite helpful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…A 1 = absorbance of extract/standard. (10,20,40,80, 100 μg/ml). The control sample consisted of 0.5 mL of RBCs mixed with hypotonic-buffered saline alone.…”
Section: Determination Of Anti-oxidant Activitymentioning
confidence: 96%
See 2 more Smart Citations
“…A 1 = absorbance of extract/standard. (10,20,40,80, 100 μg/ml). The control sample consisted of 0.5 mL of RBCs mixed with hypotonic-buffered saline alone.…”
Section: Determination Of Anti-oxidant Activitymentioning
confidence: 96%
“…Studies have found very good relationship between this simple, inexpensive, and bench-top assay and the antitumor potential of the cytotoxic compounds [10]. So, BSLB might be helpful as a preliminary screening in the antitumor drug designing and synthesis expeditions [10].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Their structures, bearing two benzene rings (A and B), are linked by an enone bridge. They have demonstrated antiproliferative activity against cancer cells, including breast cancer [13][14][15] . Mai et al described chalcone was effective against ERpositive breast cancer cells (MCF-7 line) targeting 20 apoptotic markers 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Brine shrimp lethality (BSL) assay has been shown to have a good correlation with other antitumor assays. The BSL model has proved helpful as a preliminary screening model in the drug design and synthesis of cytotoxic compounds (Nazir et al, 2013). The lethality of the extracts on the brine shrimps was classified by Padmaja et al (2002).…”
Section: Discussionmentioning
confidence: 99%